Susceptible Stages in Schwann Cells for NF1-Associated Plexiform Neurofibroma Development - Le, Lu Q. (2011)
Stem cells are under strict regulation by both intrinsic factors and the microenvironment. There is increasing evidence that many cancers initiate through acquisition of genetic mutations (loss of intrinsic control) in stem cells or their progenitors, followed by alterations of the surrounding microenvironment (loss of extrinsic control). In Neurofibromatosis Type 1 (NF1), deregulation of Ras signaling results in development of multiple neurofibromas, complex tumors of the peripheral nerves. Neurofibromas arise from the Schwann cell lineage following loss of function at the NF1 locus, which initiates a cascade of interactions with other cell types in the microenvironment as well as additional cell autonomous modifications. In this study, we sought to identify whether a temporal “window of opportunity” exists during which cells of the Schwann cell lineage can give rise to neurofibromas following loss of NF1. We show that acute loss of NF1 in both embryonic and adult Schwann cells can lead to neurofibroma formation. However, the embryonic period when Schwann cell precursors and immature Schwann cells are most abundant coincides with enhanced susceptibility to plexiform neurofibroma tumorigenesis. This model has important implications for understanding early cellular events that dictate neurofibroma development, as well as for the development of novel therapies targeting these tumors.